2007
DOI: 10.1118/1.2795829
|View full text |Cite
|
Sign up to set email alerts
|

Guiding curve based on the normal breathing as monitored by thermocouple for regular breathing

Abstract: Adapting radiation fields to a moving target requires information continuously on the location of internal target by detecting it directly or indirectly. The aim of this study is to make the breathing regular effectively with minimizing stress to the patient. A system for regulating patient's breath consists of a respiratory monitoring mask (ReMM), a thermocouple module, a screen, inner earphones, and a personal computer. A ReMM with thermocouple was developed previously to measure the patient's respiration. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
2
23
1
Order By: Relevance
“…Therefore, faster scan times were observed with VBF while also reducing breathing irregularities. Our results were consistent with the literature, where 40%–55% reductions in irregularity were observed when using visual and audiovisual biofeedback systems, 18 , 19 respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, faster scan times were observed with VBF while also reducing breathing irregularities. Our results were consistent with the literature, where 40%–55% reductions in irregularity were observed when using visual and audiovisual biofeedback systems, 18 , 19 respectively.…”
Section: Discussionsupporting
confidence: 93%
“…However, because this 4D MRI algorithm is prospectively triggered based on amplitude, long acquisition times were reported due to recurring pauses arising from highly irregular breathing patterns 14 , 15 , 16 . It has been shown that incorporating audio coaching and visual biofeedback (VBF) into 4D CT acquisition and radiation therapy delivery improves breathing regularity, increases anatomic reproducibility, and reduces the overall time burden of these procedures 17 , 18 , 19 . Given long 4D MRI exam times, efforts to reduce breathing irregularities are advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that AV biofeedback can result in significant reductions in the variability of both the period and the amplitude of a subject's breathing pattern [2,6,9,15,16]. An average improvement of 38 % has been seen in the RMSE in displacement, 82 % in the RMSE in Period, and 44 % in the baseline drift for individual breathing traces [9].…”
Section: Discussionmentioning
confidence: 99%
“…Breathing session 1: 1.426 Breathing session 2: 0.926, a larger discrepancy between free breathing and breathing guidance regularity (p = 0.212) e Pollock: RMSE between breathing signal and predicted breathing position patient to match their own breathing to, 54 and combinations thereof. 58,64,65 In addition to the nature of guiding prompts utilized, study design has also factored into influencing patient acceptance and compliance with the breathing guidance intervention.…”
Section: Displacement Of Internal Target Volume (Itv)mentioning
confidence: 99%